2020
DOI: 10.1111/acer.14411
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Alcohol Consumption With Vascular Structure and Arterial Stiffness in the Spanish Population: EVA Study

Abstract: Background Controversy exists regarding the way alcohol use is associated with vascular structure and arterial stiffness parameters. The purpose of this study is to evaluate the association between alcohol consumption with vascular structure and arterial stiffness in an adult population. Methods We conducted a cross‐sectional study. Five hundred and one participants were recruited by random sampling from an urban population of 43,946 individuals aged 35 to 75 years, assigned from 5 healthcare centers located i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 57 publications
2
17
0
1
Order By: Relevance
“…The 13 studies in the current review ( Table 2 ) [ 13 , 14 , 15 , 16 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] included 23,489 participants (9 studies investigating both sexes and 4 only males). Most studies involved more than 250 participants while few had less than 20.…”
Section: Qualitative Analysis (Systematic Review)mentioning
confidence: 99%
See 2 more Smart Citations
“…The 13 studies in the current review ( Table 2 ) [ 13 , 14 , 15 , 16 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] included 23,489 participants (9 studies investigating both sexes and 4 only males). Most studies involved more than 250 participants while few had less than 20.…”
Section: Qualitative Analysis (Systematic Review)mentioning
confidence: 99%
“…The summary of the main findings of the included studies on the association between alcohol consumption and PWV is reported in Table 4 . Of the 13 studies included, a J-shaped association between alcohol consumption and PWV was found in 5 [ 13 , 16 , 35 , 36 , 38 ], whilst a linear association was highlighted in 4 [ 14 , 34 , 39 , 40 ] and a positive benefit of alcohol consumption on arterial stiffness in 4 [ 15 , 32 , 33 , 37 ].…”
Section: Qualitative Analysis (Systematic Review)mentioning
confidence: 99%
See 1 more Smart Citation
“…Предполагаемый механизм такого эффекта -легкое седативное действие такой дозы алкоголя. Тем не менее, в популяционном исследовании EVA в Испании показано, что, хотя наибольший уровень CAVI и был при потреблении >70 г/л алкоголя в нед (8,5±1,4), но после корректировки на возраст, пол, статус курения, диету и физическую активность не отмечено статистически значимых различий в значениях Assessment of arterial stiffness using CAVI Оценка артериальной жесткости с помощью CAVI CAVI при различном уровне еженедельного потребления алкоголя (р=0,141) [46]. В исследовании D. Kume и соавт.…”
Section: влияние медикаментозной терапии и модификации поведения на Caviunclassified
“…Additionally, arterial stiffness is a strong independent predictor of cardiovascular events and mortality ( Laurent et al, 2001 ). Studies have identified and characterized the stimuli that accelerate arterial stiffness, such as smoking ( Thitiwuthikiat et al, 2017 ), alcohol ( Gonzalez-Sanchez et al, 2020 ), insufficient sleep ( Chami et al, 2016 ), inactivity, and sedentariness ( O’Donovan et al, 2014 ). Thus, the prevention of cardiovascular events has become a crucial strategy for cardiovascular disease diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%